Water‐Soluble Photoinitiators from Dimethylamino‐Substituted Monoacylphosphine Oxide for Hydrogel and Latex Preparation. Issue 19 (13th August 2021) - Le, Cuong Minh Quoc; Petitory, Tatiana; Wu, Xingyu; Spangenberg, Arnaud; Ortyl, Joanna; Galek, Mariusz; Infante, Lorena; Thérien‐Aubin, Héloïse; Chemtob, Abraham
Abstract: In order to respond to the growing demand for radiation‐curable waterborne products like hydrogels or inks, there is a need for water‐soluble radical photoinitiators exhibiting absorption in the near UV to visible range. Herein the synthesis of a novel type‐I diphenylphosphine oxide photoinitiator bearing a 2, 6‐dimethyl‐4‐dimethylaminobenzoyl group is described. The presence of a tertiary amino group in the para position of the benzoyl group results in an increased absorption in the visible range and its facile conversion into water‐soluble derivatives after a subsequent protonation or quaternization reaction. Quaternization with methyl triflate (MeOTf) yields a water‐soluble monoacylphosphine oxide compound displaying a quaternary ammonium group N(CH3 )3 + OTf − . The main characteristics are water‐solubility, shelf‐stability, absorption in near‐UV range, low cytotoxicity, and efficient α ‐scission as evidenced by steady‐state photolysis experiments. Its photopolymerization efficiency has been evaluated by real‐time Fourier transform infrared spectroscopy at 385 and 420 nm using an aqueous solution of poly(ethylene glycol) acrylate. The polymerization rate is comparable to that obtained with the conventional water‐soluble monoacylphosphine oxide TPO‐Li. Using this new photoinitiator, 3D‐printed hydrogels, and aqueous polymer dispersions can be prepared. Abstract : An approach to synthesizing new water‐soluble radical photoinitiators based on ammonium salts of benzoyl (diphenyl)phosphine oxide is presented.